Embedding web-based geographic information system (web-based gis) in teaching and learning of history - Zainol, R.; Yacob, S.P. (2014)
Current education system requires innovative approach in enhancing students’ understanding in any subjects. One of the innovative approaches that can be implemented in teaching and learning is web based geographic information system (web-based GIS). Not only it is easy to use, it is also freely available online. Therefore this study explores the tools available in the current web-based GIS in teaching and learning of history subject. The method used in this study is through experiments in using the web-based GIS tools namely Google Earth in the Malaysian Form Five history curriculum. For each topic that requires the use of map, Google Earth tools are evaluated. Results show almost all tools available in Google Earth can be used in all topics that need the application of high-order thinking skills (HOTs). Therefore it is timely that web-based GIS is used as one of the innovative approaches used in education policy.